Preacher, book four - Ennis, Garth (Vertigo/DC Comics, 2014)
"Preacher Jesse Custer's dark journey to find God, accompanied by his gun-toting girlfriend and Irish vampire buddy, continues. During some down time, Jesse Custer faces an enemy from the past, who seeks vengeance for his father's death. Also includes a story spotlighting the Saint of Killers and a standalone tale starring Cassidy, the vampire. This volume collects PREACHER #34-40, PREACHER SPECIAL: ONE MAN'S WAR, PREACHER SPECIAL: THE GOOD OLD BOYS, PREACHER SPECIAL: THE STORY OF YOU-KNOW-WHO."--